PERANCANGAN PROTOTYPE APLIKASI PENGOLAHAN DAFTAR BARANG INVENTARIS (RUANGAN) PADA FAKULTAS TEKNIK DAN ILMU KOMPUTER (FTIK) UNIVERSITAS MUHAMMADIYAH KOTABUMI - Khusnul Khotimah (LPPM Universitas Muhammadiyah Kotabumi, 2021)
Inventory management is the process of controlling and managing the assets and goods owned by an organization. At FTIK (Faculty of Information Technology and Computer Science), Muhammadiyah University Kotabumi, there are various types of equipment and items that need to be inventoried, such as computer devices, laboratory equipment, and other tools. The prototype design of the room inventory list processing application is a response to the issues identified during the problem identification phase. The modeling of this application is done using a Use Case Diagram as its visual representation. The application designed in this research is intended for processing the room inventory list, using electronic devices as the processing tool for all transactions related to room inventory list management. The design aims to improve efficiency in inventory management by reducing delays and errors in the inventorying, recording, monitoring, and reporting of room inventory items